DIAPH3 governs the cellular transition to the amoeboid tumour phenotype - Martin H. Hager; Samantha Morley; Diane R. Bielenberg; Sizhen Gao; Matteo Morello; Ilona N. Holcomb; Wennuan Liu; Ghassan Mouneimne; Francesca Demichelis; Jayoung Kim; Keith R. Solomon; Rosalyn M. Adam; et al. (EMBO Molecular Medicine, 2012)
Abstract Therapies for most malignancies are generally ineffective once metastasis occurs. While tumour cells migrate through tissues using diverse strategies, the signalling networks controlling such behaviours in human tumours are poorly understood. Here we define a role for the Diaphanous‐related formin‐3 (DIAPH3) as a non‐canonical regulator of metastasis that restrains conversion to amoeboid cell behaviour in multiple cancer types. The DIAPH3 locus is close to RB1, within a narrow consensus region of deletion on chromosome 13q in prostate, breast and hepatocellular carcinomas. DIAPH3 silencing in human carcinoma cells destabilized microtubules and induced defective endocytic trafficking, endosomal accumulation of EGFR, and hyperactivation of EGFR/MEK/ERK signalling. Silencing also evoked amoeboid properties, increased invasion and promoted metastasis in mice. In human tumours, DIAPH3 down‐regulation was associated with aggressive or metastatic disease. DIAPH3‐silenced cells were sensitive to MEK inhibition, but showed reduced sensitivity to EGFR inhibition. These findings have implications for understanding mechanisms of metastasis, and suggest that identifying patients with chromosomal deletions at DIAPH3 may have prognostic value.